Anti-fatigue activity and mechanism of crocetin loaded nanoliposome in acute exercise-treated mice - Jian Nan; Jinglei Li; Haishan Wu; Haoran Cheng; HyunJin Park; Qingsheng Zhao; Liu Yang (Food Science and Human Wellness)
Crocetin displays strong antioxidant, anti-inflammatory and anti-depression activity which is promising to relieve symptoms of fatigue. As a carotenoid, crocetin is difficult to dissolve in water and highly unstable against many environmental factors. Nanoliposome is used to encapsulate crocetin to improve its water dispersion. In the present study, the antifatigue activities and potential mechanism of crocetin loaded nanoliposome (CLN) was extensively investigated. The potential antifatigue pathway of CLN was analyzed. Furthermore, impact of CLN on the gut microbiota structure was examined which contributes to its antifatigue functions. CLN significantly increases exhaustive swimming time of fatigue mice, decreases the blood contents of lactic, blood urea nitrogen (BUN) and malondialdehyde (MDA). At the same time, CLN improves the activity of glutathione peroxidase (GSH-Px) and succinate dehydrogenase (SDH) enzyme, attenuates the oxidant stress in mice. CLN activates the adenosine monophosphate-activated kinase (AMPK)/peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) signaling pathway of fatigue mice, increases the mRNA expression of ATP synthase. It also increases mRNA expression of mitochondrial transcription factor A (TFAM) which promotes mitochondrial biogenesis. Additionally, CLN ameliorates the gut microbiota structure by increasing the abundance of genus such as Lactobacillus in fatigue mice. In summary, CLN exerts strong anti-fatigue properties by decreasing the oxidant stress and the contents of harmful metabolites, augmenting the production of ATP, and potentially ameliorating the gut microbiota structure.